Porphyromonas gingivalis as a potential community activist for disease - Darveau, R P; Hajishengallis, G; Curtis, M A (Journal of dental research, 2012)
An extensive analysis of dental plaque samples over the years has led to the identification of "red" complex oral bacteria that have a strong association with each other and with disease. Consequently, these bacteria have been labeled 'periopathogens'. Studies with one of these bacteria, Porphyromonas gingivalis, have revealed that it contains several different mechanisms which either impede or modulate periodontal protective mechanisms. In a mouse model of periodontitis, it has been shown that modulation of complement function by P. gingivalis facilitates a significant change in both the amount and composition of the normal oral microbiotia. This altered oral commensal microbiota is responsible for pathologic bone loss in the mouse. Thus, P. gingivalis creates a dysbiosis between the host and dental plaque, and this may represent one mechanism by which periodontitis can be initiated. We have therefore termed P. gingivalis a keystone pathogen.